2020
DOI: 10.1186/s12879-020-04956-1
|View full text |Cite
|
Sign up to set email alerts
|

Measles and mumps outbreaks in Lebanon: trends and links

Abstract: Background: Lebanon has experienced several measles and mumps outbreaks in the past 20 years. In this article, a case-based surveillance of both measles and mumps outbreaks in Lebanon was carried out in an attempt to outline factors contributing to the failure of elimination plans and to provide potential solutions. The relationship between the outbreaks of both diseases was described and explored. Methods: A retrospective descriptive study of confirmed cases of measles and mumps in Lebanon between 2003 and 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…During the pandemic, the health of refugees deteriorated, as the crowded conditions in tents provided little protection from the virus. In addition, immunization campaigns have been arrested, including delays in vaccinations of preventable illnesses that are already more prevalent in the refugee population, such as the highly contagious measles virus [ 4 ].…”
mentioning
confidence: 99%
“…During the pandemic, the health of refugees deteriorated, as the crowded conditions in tents provided little protection from the virus. In addition, immunization campaigns have been arrested, including delays in vaccinations of preventable illnesses that are already more prevalent in the refugee population, such as the highly contagious measles virus [ 4 ].…”
mentioning
confidence: 99%
“…Studies have shown that Syrian refugees in Lebanon live in poor conditions and suffer mostly from communicable diseases and diseases affecting women 16 . Despite efforts to provide healthcare to these vulnerable populations, outbreaks of many infectious diseases took place 17 , and cases of AFP kept increasing throughout the years. The incidence rate stabilized from 2017 till 2019 ranging from 4.14 and 4.96 per 100,000, respectively.…”
Section: Trends Of Afpmentioning
confidence: 99%
“…Mothers brought in their children's vaccination cards along with a document from the public school to ascertain the child's recent immunization status. This was a law passed by the Lebanese government in 2013 that insisted on obligatory vaccination in public schools or else the children won't continue the academic year (El Zarif et al, 2020). This means that with this practice, more caretakers are fulfilling immunization requirements compared to developed countries that are still showing vaccination hesitancy when it comes to school entry vaccines (McNeil et al, 2019).…”
Section: Immunization Practice Indicatorsmentioning
confidence: 99%
“…As for vaccinations, the Lebanese MOPH and PHC centers are doing a great job in providing vaccines and knowledge attitude and practice interventions in the literature are showing positive results, but more focus should be done in remote areas where measles and mumps are suspected to reemerge (El Zarif et al, 2020). Therefore, more in depth assessment of vaccination coverage is needed in Lebanon to reach the target above 95 % as suggested by the WHO -EPI.…”
Section: Practical Suggestions For Future Community Basedinterventionsmentioning
confidence: 99%
See 1 more Smart Citation